Magnetic resonance findings of the corpus callosum in canine and feline lysosomal storage diseases. - Daisuke Hasegawa (Public Library of Science (PLoS), 2013)
Several reports have described magnetic resonance (MR) findings in canine and feline lysosomal storage diseases such as gangliosidoses and neuronal ceroid lipofuscinosis. Although most of those studies described the signal intensities of white matter in the cerebrum, findings of the corpus callosum were not described in detail. A retrospective study was conducted on MR findings of the corpus callosum as well as the rostral commissure and the fornix in 18 cases of canine and feline lysosomal storage diseases. This included 6 Shiba Inu dogs and 2 domestic shorthair cats with GM1 gangliosidosis; 2 domestic shorthair cats, 2 familial toy poodles, and a golden retriever with GM2 gangliosidosis; and 2 border collies and 3 chihuahuas with neuronal ceroid lipofuscinoses, to determine whether changes of the corpus callosum is an imaging indicator of those diseases. The corpus callosum and the rostral commissure were difficult to recognize in all cases of juvenile-onset gangliosidoses (GM1 gangliosidosis in Shiba Inu dogs and domestic shorthair cats and GM2 gangliosidosis in domestic shorthair cats) and GM2 gangliosidosis in toy poodles with late juvenile-onset. In contrast, the corpus callosum and the rostral commissure were confirmed in cases of GM2 gangliosidosis in a golden retriever and canine neuronal ceroid lipofuscinoses with late juvenile- to early adult-onset, but were extremely thin. Abnormal findings of the corpus callosum on midline sagittal images may be a useful imaging indicator for suspecting lysosomal storage diseases, especially hypoplasia (underdevelopment) of the corpus callosum in juvenile-onset gangliosidoses.